Relationship Between Job Stress and Job Performance Among Hospital Staff Nurses in Sanandaj, Kurdestan, Iran - Gazanizad, Neda (2010)
A descriptive, correlational study was conducted to investigate the relationship between job stress and job performance among hospital staff nurses and to compare job stress and job performance between intensive care unit and non-intensive care unit nurses. Data were collected by using questionnaires which included the Nursing Stress Scale, Schwirian Six Dimension Scale of Nursing erformance, and a demographic questionnaire. Five hundred and thirty questionnaires was distributed among nurses in three public hospitals and 428 were returned (response rate was = 81%). Three hundred and one respondents were from on-intensive Care Units (70%) and 127 (30%) from Intensive Care Units. Pearson Product Moment correlations revealed statistically positive significant direct correlation between job stress and job performance (r = .20, p<.05). It means nurses who reported high levels of job stress appraised their performance at correspondingly high levels. This implies more stress leads to more challenges which in turn lead to optimal performance. Results indicated that Intensive Care Unit nurses have higher mean job stress scores (1.44±0.58) than non-Intensive Care Unit nurses (1.32 ± 0.65) but it were not significant. Mean job performance scores were significantly higher in Intensive Care Unit nurses (3.18 ± 0.44) than non-Intensive Care Unit nurses (3.03 ± 0.44). Of the demographic variables, significant differences in stress scores were found for types of unit, education levels, years of experience, and sole bread winner versus non sole bread winner. Also job performance scores were significantly different for type of unit, marital status, worked shift, and sole bread winner versus non sole bread winner. These findings are important and useful to hospital administrators and can help in developing appropriate coping strategies to stress and hence to reduce stress of nurses working in all the units of a hospital specially in Intensive Care Unit nurses.